Development of a magnetic resonance imaging protocol to visualize encapsulated contrast agent markers in prostate brachytherapy recipients: initial patient experience - Lim, Tze Yee; Kudchadker, Rajat J.; Wang, Jihong; Bathala, Tharakeswara; Szklaruk, Janio; Pugh, Thomas J.; Mahmood, Usama; Ibbott, Geoffrey S.; Frank, Steven J. (Journal of Contemporary Brachytherapy, 2016)
Purpose : Computed tomography (CT)-based prostate post-implant dosimetry allows for definitive seed localization but is associated with high interobserver variation in prostate contouring. Currently, magnetic resonance imaging (MRI)-based post-implant dosimetry allows for accurate anatomical delineation but is limited due to inconsistent seed localization. Encapsulated contrast agent markers were previously proposed to overcome the seed localization limitation on MRI images by placing hyperintense markers adjacent to hypointense seeds. The aim of this study was to assess the appearance of these markers in prostatic tissue, and develop an MRI protocol to enable marker visualization. Material and methods : We acquired MRI scans in prostate implant patients (n = 10) on day 0 (day of implant) and day 30 (month after implant). Before implantation of the markers, the routine post-implant MRI protocol included a 3D T2-weighted fast-spin-echo (FSE) sequence with which markers and seeds could not be clearly visualized. To visualize the MRI markers, a 3D fast radiofrequency-spoiled gradient-recalled echo (FSPGR) sequence was evaluated for marker and seed visibility, as well as prostate boundary definitions. Results : The 3D FSPGR sequence allowed for the visualization of markers in the prostate, enabling the distinction of signal voids as seeds versus needle tracks. The updated post-implant MRI protocol consists of this 3D FSPGR scan and an optional 3D T2-weighted FSE scan. The optional 3D T2-weighted FSE sequence may be employed to better visualize intraprostatic detail. We also described the observed image artifacts, including seed susceptibility, marker chemical shift, partial volume averaging, motion, and wraparound artifacts. Conclusions : We have demonstrated an MRI protocol for use with hyperintense encapsulated contrast agent markers to assist in the identification of hypointense seeds.